Discussion on Myths of Female Heroes in Respect of Gender Socialisation: an Alternative Activity for EFL College Students in Doing a Literary Analysis - Leni Marlina (Universitas Negeri Padang, 2014)
Myths, tales and other related stories for children have significant role in all cultures since they can render the multiplicity of experiences; explain the behaviour of the physical universe; and describe human nature and society. These stories are ‘the most potent means by which perceptions, values and attitudes are transmitted from one generation to the next’ (Hourigan 1997, p.1). One genre of such stories is hero story. The hero story is very popular in children’s literature and young adult literature since they are considered to be ‘unequivocally good for children morally and mentally’ (Hourigan 1997, p.3). To see how the heroic archetype has changed over time, we can explore and compare the journey of traditional female heroes with a contemporary female superhero. This research paper shows how to do an alternative activity for EFL (English as Foreign Language) college students in doing literary analysis by discussing the journey of three female heroes from ancient Greek myths and a recently young adult (YA) text. The heroines of the ancient myths are Psyche in Apuleius’s Cupid and Psyche (1855); and Artemis in Callimachus’s Artemis (1988). The heroine of the YA literature is Katniss in Collin’s The Hunger Games (2008), a contemporary young adult’s dystopian literature. By patterning the quests of the heroes in question onto Campbell’s monomyth, the author tries to demonstrate that these female heroes (Psyche, Artemis and Katniss) qualify as male heroes. Then, the author compares and contrasts the female heroes in respect of contemporary gender theory and the socialisation of girls.